Effects of national volume-based procurement policy on the usage and expenditure of platinum antineoplastic drugs in China: an interrupted time series study - Yu, Xihui; Lin, Hailing; Li, Bin; Fu, Hongbo; Zhang, Yaofeng (Frontiers in Pharmacology, 2025)
ObjectiveDigestive tract tumors are the common tumors in China. Platinum-based chemotherapy drugs, especially oxaliplatin, play an important role in the treatment of gastrointestinal tumors. Starting from October 2021, the fifth national centralized volume-based procurement (NCVBP) was implemented in China to reduce the price of oxaliplatin. However, the effect of the policy on platinum antineoplastic drugs is uncertain. This study aims to explore the impact of NCVBP policy on the usage and expenditure of platinum antineoplastic drugs in China.MethodsOxaliplatin and alternative drugs were used as objects of study to explore the impact of NCVBP policy from the first quarter of 2017 to the second quarter of 2024, while October 2021 was the implementation time point of the policy. Quarterly data was collected from the Chemical Drug Terminal of China’s Public Medical Institutions database in 1,805 sample public hospitals and more than 3,000 urban public hospitals in China. Descriptive analysis was conducted using purchase volume, expenditure and daily cost as variables. Interrupted time-series (ITS) analysis was applied to further analyze the effect of NCVBP policy on the medicines under study.ResultsThe average volume of bid-winning drug of oxaliplatin increased by 623.66% after the implementation of the policy, and its expenditure increased by 7.92%. The decline in price had promoted the increase in consumption, and the policy had realized the exchange of price for quantity. After the implementation of NCVBP, a significant increase was associated with the volume of bid-winning drugs (P < 0.001) and the trend change was statistically significant (P < 0.001), with an upward trend. The volume of non-winning drugs and the branded drug decreased immediately after policy intervention (P < 0.001), but there was no obvious downward trend change following. ITS analysis indicated that there were no significant differences in level and trend changes for expenditure of in alternative drugs.ConclusionThe policy had an influence on promotion of generic substitution and the decrease in expenditures for platinum antineoplastic drugs while ensuring the usage of drugs. The third-generation platinum antineoplastic medications introduced into the fifth NCVBP policy had no major influence on the use of first- and second-generation platinum antineoplastic treatments. Although the general situation for alternative pharmaceuticals was largely steady, with no expected increase in costs and expenditures, monitoring of alternative drugs was required.